Comparative analysis of nitrate content in fruit and vegetable products by HPLC - S. V. Koptsev; S. V. Glazkov (Овощи России, 2019)
Relevance. The quality of food products in Russia and delivered to retail chains for mass consumption is currently one of the most important food safety priorities.Methods. The article contains the results of studies of nitrate content in fruit and vegetable products during 2018-2019 period, obtained from VNIITeK laboratory, comparisons were made with the permissible level of Maximum residue levels (MRL) for nitrate, which are set in Technical regulation TR TS 021/2011. Totally, 252 samples were studied, for the period from January 2018 to April 2018 inclusive 2019.Results. The nitrate content was determined by liquid chromatography. It was shown, that content of nitrate ions in fruit and vegetable products varies in a wide range, depending on the selected group, at the same time, the lowest level of nitrate is established in children 's fruit puree, the highest levels are found in tomato sauce.